Descrição de uma nova espécie de Micrurus do Estado de Roraima, Brasil (serpentes, elapidae) - Carvalho, Celso Morato de (Papéis Avulsos de Zoologia, 2002)
Micrurus pacaraimae, sp. n.,from Vila Pacaraima, Roraima, Brasil/ Venezuela border (04o 31'N, 61o 09'W), is characterized by: 201 ventrals; 43 subcaudals; no supra-analtubercles; anal divided; black cephalic cap in contactwith lhe nuchal black ring on the posterior margin of the parietals; throat white; black and red single rings on body and tail.